PHP Objects, Patterns, and Practice - Zandstra, Matt.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
This book takes you beyond the PHP basics to the enterprise development practices used by professional programmers. Updated for PHP 5.3 with new sections on closures, namespaces, and continuous integration, this edition will teach you about object features such as abstract classes, reflection, interfaces, and error handling. You$1 (Bll also discover object tools to help you learn more about your classes, objects, and methods. Then you$1 (Bll move into design patterns and the principles that make patterns powerful. You$1 (Bll learn both classic design patterns and enterprise and database patterns with easy-to-follow examples. Finally, you$1 (Bll discover how to put it all into practice to help turn great code into successful projects. You$1 (Bll learn how to manage multiple developers with Subversion, and how to build and install using Phing and PEAR. You$1 (Bll also learn strategies for automated testing and building, including continuous integration. Taken together, these three elements$1 (Bobject fundamentals, design principles, and best practices$1 (Bwill help you develop elegant and rock-solid systems.s
PHP: Design and Management -- Objects -- PHP and Object -- Object Basic -- Advanced Featurers -- Object Tools -- Object and Design -- Patterns -- What are Design Pattern? Why Use Them? -- Some Pattern Principles -- Generating Object -- Pattern for Flexible Object Programming -- Performing and Representing Tasks -- Enterprise Patterns -- Database Patterns -- Practice -- Good (and Bad) Practice -- An Introduction to PEAR and Pyrus -- Generating Documentation with phpDocumentor -- Version Control with Subversion -- Testing with PHPUnit -- Automated Build with Phing -- Continuous Integration -- Conclusion -- Objects, Patterns, Practice.
Keywords: Computer science; Computer Science; Programming Techniques